O PNAES na UFC - Campus Fortaleza: uma avaliação do Programa de Assistência Estudantil ofertado na PRAE, no período de 2013-2017 - Marinho, Priscila Gonçalves (2017)
The purpose of this study was to evaluate the UFC-Campus Fortaleza Student Assistance Program, aimed at students in situations of socioeconomic vulnerability, through the Pro-Rectory of Student Affairs-PRAE, as part of the implementation of the National Program of Student - PNAES. For this, starting from a socio-historical conception of education,we problematize a path to higher education in Brazil, traditionally enjoyed by the dominant classes, as well as situate aspects related to the punctual and fragmented actions of student assistanceto the few poor people who entered public universities,noting that, until the establishment of the PNAES, no specific budget resources had been allocated for this purpose. The PNAES emerged from a neo-developmental context that caused contemporary transformations in the Brazilian Higher Education Policy, through measures aimed at democratizing access to this level of education, and as a strategy to ensure the conditions of poor students who entered university, arguing that the right of access differs from the right to remain in those institutions. In this perspective, the theoretical-methodological path of this research was based on the Marxist critical-dialectical method, together with elements of the methodology of in-depth evaluation of public policies, which concern the dimensions of context analysis, content, institutional trajectory, territorial and temporal spectra of the program. It had a qualitative nature and it was used documentary and bibliographical research for the immersion in categories of analysis of the research, which dealt with university, poverty and equity. In addition, he used field research using the following techniques: participant observation, field diary and semi-structured interviews, which were applied with professionals, responsible for the operationalization of the program, as well as with students who are beneficiaries of the services, programs and aids offered. It presented as main results the contributions of student assistance in the university life of the student, while acting from a perspective of equity with a view to alleviating unequal situations, arising from the "social question", poverty and its different repercussions. It also identified that the services offered by the PRAE cover almost all of the areas established by the PNAES, as well as broad to attend to the subjective dimensions of the students. However, despite the distant existence of the PRAE, the regulation of its local program occurred only after the establishment of the PNAES, and therefore took place late and without the participation of professionals and students. From this, the urgent construction of collective spaces of social control over the program is considered. Regarding the aspects of its implementation, although it contributes significantly to the students' university life, it still serves a restricted public in the face of the growing demand for student assistance, indicating a focused scope and the need for more investments in the area. In addition, the institutional working conditions available to the team are not favorable to a more qualified program offer. Finally, in times of dismantling of public policies, the struggle to maintain and expand the PNAES and its transformation into a state policy must be the focus to be pursued.